Characteristics of Psychiatric Emergency Situations and the Decision-Making Process Leading to Involuntary Admission - Marty, Silvan; Jaeger, Matthias; Moetteli, Sonja; Theodoridou, Anastasia; Seifritz, Erich; Hotzy, Florian (Frontiers in Psychiatry, 2019)
Introduction: Involuntary admissions to psychiatric hospitals, regardless of their beneficial effects, violate the patients' autonomy. To keep such measures at a minimum and develop less restricting and coercive alternatives, a better understanding of the psychiatric emergency situations which end up in involuntary admissions is needed. This descriptive and exploratory study investigates the consultations leading to involuntary admission and the decision-making process of the referring physicians. Methods: We developed an online questionnaire to collect data on the characteristics of the consultation leading to an involuntary admission, including influencing factors from the referring physicians‘ perspective, as well as their professional background. We included 107 physicians who completed the questionnaire after they had referred patients for involuntary admission to one major psychiatric hospital in Switzerland. Results: The referring physicians were heterogeneous regarding their medical background and experience with psychiatric emergency situations. The consultations were time consuming and took place in various locations. Clinical findings, third-party anamnesis and a known psychiatric diagnosis contributed strongest to the decision to admit involuntarily. “Protection from danger to self” was named most frequently as purpose of the admission. Discussion: This study emphasizes the variety of psychiatric emergency situations leading to involuntary admissions. In most cases, several parties are involved and influence the decision together with medical and social factors. To reduce the number of involuntary admissions, alternatives for patients with a high symptom load and at risk of harming themselves are needed. Possible approaches to achieve that reduction and recommendations for further research are provided.